The global economic crisis - challenge to economic concepts and policies - what next - Trenovski, Borce (Faculty of Economics – Skopje, University Ss. Cyril and Methodius, Skopje, 2014)
The end of the twentieth and the beginning of the twenty first century were marked by a general consideration in the economic science (numerous books, papers, public debates, conferences etc.) that there were no serious threats of large economic fluctuations, that the business cycle was “dead”, and that the economic policy was able to successfully handle any challenge. However, the contemporary economic crisis spread doubt on those views, thus endangering not only the fundaments of economic policy, but also their theoretical foundation. The global economic crisis actualized the issues and dilemmas concerning the designing of the key macroeconomic policies – their mutual interactions, as well as their efficiency and effects on the macroeconomic environment. This paper clearly shows the gap between economic theory and economic policy that was made by the global crisis; the paper determines that the Keynesian economic theory was a dominant part in economic policies undertaken when crisis appears; at the end the paper provides an answer that the question of whether to choose the state or the market, the Keynesianism or neoliberalism is primarily determined by the actual situation in each economy, region, continent and globally. Also it should be noted that the optimal mix of economic concepts represents a major determinant of both the efficiency of economic policies and the problemsolving in economic practice.
Keywords: economic concepts, economic policy, economic cycles, global economic crisis